Seroprevalensi Kasus Toxoplasmosis sebagai Infeksi Oportunistik pada Penderita HIV/ Acquired Immune Deficiency Syndrome (AIDS) Di Kabupaten Sidoarjo - Andi Jayawardhana; Harnida, Hanna; Dewi Purwatiningsih; Heni Puspitasari; Mufasirin; Lucia Tri Suwanti; Arif Rahman Nurdianto (NERSMID : Jurnal Keperawatan dan Kebidanan, 2023)
Toxoplasma gondii is an obligate intracellular parasite that can cause toxoplasmosis infection. About 60% of the world's population has been infected. Toxoplasma cerebri is one of the most common opportunistic infections in the central nervous system of HIV patients. The disease is acute and chronic, with mild symptoms that are non-specific so it is difficult to distinguish from other diseases or is often asymptomatic. The incidence of Human Immunodeficiency Virus (HIV) occupies the highest place in Asia with high morbidity and mortality. Toxoplasma is ranked in the top 10 opportunistic diseases as a direct cause of morbidity and mortality, with variable symptoms and reactivation. The purpose of the study: to detect Toxoplasma gondii from blood samples of patients with HIV/Acquired Immune Deficiency Syndrome (AIDS). In immunocompromised conditions, especially HIV/AIDS, symptoms of severe complications will arise, one of which is toxsoplasma encephalitis (TE). The high rate of morbidity and mortality of TE in HIV/AIDS patients, around 30-40%, makes an accurate diagnosis important. Research Methods: The study design used was cross sectional to determine the level of IgG Toxoplasma Gondii antibodies in HIV patients and serologically. The research subjects were 30 individual subjects who were positive for HIV infection, of which 30 patients would be screened for the levels of IgG Toxoplasma Gondii antibodies and then see the correlation with lifestyle and food consumed. The achievement target of this research is to find out whether HIV patients have levels of IgG Toxoplasma Gondii antibodies through serological tests, so that appropriate therapy and education can be given for the treatment of toxoplasmosis, so that these results can be published scientifically in national journals, and become paper material in scientific meetings.